The Effectiveness of Educational Games for Enhancing Early Reading Skills among Children with Intellectual Disabilities - Hartati, Peby Tri; Derin, Tatum Derin; Hasanah, Nisaul; Novembli, Meta Silfia; Hanesty, Ebnovrio (Journal of English Language and Education, 2026)
Early reading skills are essential for academic learning; however, children with mild intellectual disabilities frequently experience persistent difficulties in decoding simple syllabic word structures such as consonant–vowel–consonant–vowel (CV–CV), which limits their early reading development. This study aimed to examine the effectiveness of the GEMMAS educational game in improving early reading skills of children with mild intellectual disabilities. The study employed a Single Subject Research approach with an A–B–A design. The participant was a fifth-grade student with mild intellectual disabilities at Sekolah Luar Biasa Negeri 1 Yogyakarta. Data were collected through oral and performance tests and analyzed using visual graphical analysis. The results showed an improvement in reading skills from 0% during the baseline phase to a stable level of 60% after the intervention, indicating that the GEMMAS educational game effectively enhances early reading skills.